Anti-Tumor Drug-Loaded Oxygen Nanobubbles for the Degradation of HIF-1 alpha and the Upregulation of Reactive Oxygen Species in Tumor Cells - Khan, Muhammad Saad; Hwang, Jangsun; Lee, Kyungwoo; Choi, Yonghyun; Seo, Youngmin; Jeon, Hojeong; Hong, Jong Wook; Choi, Jonghoon (Multidisciplinary Digital Publishing Institute (MDPI), 2019)
Hypoxia is a key concern during the treatment of tumors, and hypoxia-inducible factor 1 alpha (HIF-1 alpha) has been associated with increased tumor resistance to therapeutic modalities. In this study, doxorubicin-loaded oxygen nanobubbles (Dox/ONBs) were synthesized, and the effectiveness of drug delivery to MDA-MB-231 breast cancer and HeLa cells was evaluated. Dox/ONBs were characterized using optical and fluorescence microscopy, and size measurements were performed through nanoparticle tracking analysis (NTA). The working mechanism of Dox was evaluated using reactive oxygen species (ROS) assays, and cellular penetration was assessed with confocal microscopy. Hypoxic conditions were established to assess the effect of Dox/ONBs under hypoxic conditions compared with normoxic conditions. Our results indicate that Dox/ONBs are effective for drug delivery, enhancing oxygen levels, and ROS generation in tumor-derived cell lines.